Understanding the evolution of stratified extracellular polymeric substances in full-scale activated sludges in relation to dewaterability. Issue 2 (2nd December 2014) - Zhang, Weijun; Peng, Siwei; Xiao, Ping; He, Jie; Yang, Peng; Xu, Shiwei; Wang, Dongsheng
Abstract : The dynamic variation in soluble EPS resulted into the fluctuation of activated sludge dewatering behavior in full-scale WWTPs. Abstract : Activated sludge is a highly changeable colloidal system. In this study, the dynamic variation in physicochemical characteristics, especially distribution and abundance of extracellular polymeric substances (EPS) of activated sludges from different WWTPs was investigated in order to establish the relationships between floc properties and the sludge dewatering property. Firstly, it was observed that the total EPS content of the activated sludge was significantly decreased with the rise in temperature. Three-dimensional fluorescence excitation–emission matrix (3D-EEM) spectroscopy analysis indicated that each sludge fraction (soluble EPS, loosely-bound EPS (LB-EPS), tightly bound EPS (TB-EPS) and pellet) from different WWTPs had a similar fluorescence fingerprint in the same time period. In addition, protein-like substances were found to be the dominant components in TB-EPS and pellets regardless of operating time for each WWTP sludge. At low temperatures, soluble EPS and LB-EPS also mainly contained protein-like compounds, while the amount of humic acids of them was increased significantly in the summer. According to Pearson's correlation analysis, normalized CST correlated well with the composition and content of soluble EPS, indicating that the change in soluble EPS properties caused fluctuation of sludge dewatering behavior. Finally, we proposed some operating strategies for improving the dewatering performance of activated sludge in full-scale WWTPs by regulating the soluble EPS properties.